(untitled) (Journal of Society of Surgeons of Nepal, 2020)
Mammary Tuberculosis is rare, with an incidence of 4% of all breast diseases in TB endemic countries. The clinical presentation can be non-specific and may mimic malignancy of the breast. Tis is a case report of a middle-aged male patient presenting with an ulcerated lump of the breast, diagnosed as mammary tuberculosis. Breast tuberculosis is extremely rare in males. The clinical presentation is varied and a high index of clinical suspicion is extremely essential for diagnosis with confirmation by cytology and histology. Anti-tubercular treatment (ATT) is the mainstay of treatment, with surgery being required in few indicated cases